Determination of Parameters of Moving Up and Down of the Price of a Share in the Binomial Option Pricing Model Using the Ito Lemma. A Short Research Memo - Burenin Aleksey (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
The article discusses the approach to determining the parameters of the binomial model for estimating the premium of the American stock option, which is presented in the article